PENGARUH BAURAN PEMASARAN DAN CITRA MEREK TERHADAP KEPUTUSAN BERKUNJUNG DI RUMAH MAKAN AFAT BANGKA, KELAPA GADING, JAKARTA UTARA, DKI JAKARTA - Susanto, Prayogo; Dewantara, Yudhiet Fajar; Charlie, Jovanca Nesya (Program Studi Hospitality dan Pariwisata, 2024)
Afat Bangka Restaurant is one of the traditional eateries from the Bangka Belitung region on the island of Sumatra that has migrated from its original location to DKI Jakarta, specifically in the Kelapa Gading area of North Jakarta, to introduce the distinctive flavors of its region of origin, Bangka. Through research on the influence of the marketing mix and brand image on the decision to visit this restaurant, the researcher aims to determine whether the marketing mix strategy and brand image implemented by the restaurant have impacted consumer decisions to visit. This study employs a quantitative method. The sample taken for this research consists of 100 respondents, with data collected through a Google Form questionnaire and processed using SPSS software. The testing methods applied include validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and determination coefficient analysis. The results obtained from this research indicate that the T-test shows the marketing mix variable has a partial effect on the decision to visit, while the brand image variable does not. The F-test reveals that both variables have a simultaneous effect, and the multiple linear regression test indicates that 57% of the decision to visit is influenced by these variables. The remaining 43% is influenced by other variables outside of this study. It can be concluded that the marketing mix and brand image variables collectively affect the decision to visit.